Analisis Peran Pembelajaran Berbasis Permainan dalam Meningkatkan Partisipasi Siswa pada Pelajaran PJOK - Elisa Pitria Ningsih (Journal of Salutare, 2024)
Physical Education, Sport and Health (PJOK) is an important part of the school curriculum that aims to improve students' physical fitness, motor skills and mental health. Monotonous learning can affect student participation and academic achievement. One approach that has gained attention is game-based learning. This study aims to analyze the role of game-based learning in increasing students' participation in physical education. The research method used is qualitative research. Data were collected through observations, interviews with PJOK teachers, and group discussions with students. Data analysis was conducted by identifying patterns in students' participation, students' responses to game-based learning, and its impact on students' interest in PJOK learning. Preliminary findings show that game-based learning has a positive impact on students' interest and participation. Students are more enthusiastic and actively involved in learning when using this approach. Students explained that the games made the lessons more fun. In addition, teachers also noted an increase in student participation and peer interaction during learning. Game-based learning can play a significant role in increasing students' interest and participation in PJOK subjects. The implication is that it is important to integrate this approach into learning practices in schools to enhance students' learning experiences and